Educational Process of Exceptional Children in Special Education Waraqil Jannah School - Retno Maya Sari; Fatmariza Fatmariza; Muhamad Hendro (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article was to analyse how the educational process of exceptional children in the special educational school Waraqil Jannah. This school was an excellent school who integrated with an orphanage, founded in 2012. The researchers used descriptive qualitative methods though Purwoko’s theory. Observation, interview, and documentation were used in this collecting data. While, analysing data used triangulation technique. The obtained data was to analyzed by referring to the models of Miles and Huberman analysis with the steps of data reduction, data model (data display) and the withdrawal of conclusions. The result showed that the school used curriculum based on combination from government curriculum and local curriculum, but in the process of daily learning was adjust to condition of children. Learning facilities was available. Hence it can interfere with the learning process. There was no graduate teachers’ special education who teaches at this school Keywords: Exceptional Children, Special Education School, Learning Process